(untitled) (4D Journal of Landscape Architecture and Garden Art, 2010)
As representatives of the national Európán structures for Austria, Belgium, Croatia, Denmark, Estonia, Finland, Francé, Germany, Hungary, Ireland, Italy, Latvia, Netherlands, Norway, Poland, Portugál, Spain, Sweden, Switzerland, and signatories of this Charter, we undertake to participate in Európán 10.